Socio-demographic and clinical differences in subjects with tuberculosis with and without diabetes mellitus in Brazil--a multivariate analysis. - Barbara Reis-Santos; Rodrigo Locatelli; Bernardo L Horta; Eduardo Faerstein; Mauro N Sanchez; Lee W Riley; Ethel Leonor Maciel (PLoS ONE)
Background Several studies have evaluated the relationship between diabetes mellitus (DM) and tuberculosis (TB), but the nature of this relationship is not fully understood. TB incidence may be influenced by immunosuppression from DM, but this association may be confounded by other clinical and socioeconomic factors. We aimed to assess socio-demographic and clinical differences in TB patients with and without DM. Methods Using the Brazilian national surveillance system (SINAN), we compared 1,797 subjects with TB and DM with 29,275 subjects diagnosed with TB only in 2009. We performed multivariate analysis to identify factors associated with the presence of DM among TB patients. Results Subjects with TB - DM were older; have initial positive sputum smear test (OR = 1.42, 95% CI 1.26-1.60), and were more likely to die from TB (OR = 1.44, 95% CI 1.03-2.01). They were less likely to have been institutionalized [in prison, shelter, orphanage, psychiatric hospital (OR = 0.74, 95% CI 0.60-0.93)]; developed extra pulmonary TB (OR = 0.62, 95% CI 0.51-0.75) and to return to TB treatment after abandonment (OR = 0.66, 95% CI 0.51-0.86). Conclusions Prevalence of NCD continues to rise in developing countries, especially with the rise of elderly population, the prevention and treatment of infectious diseases will be urgent. DM and TB represent a critical intersection between communicable and non-communicable diseases in these countries and the effect of DM on TB incidence and outcomes provide numerous opportunities for collaboration and management of these complex diseases in the national public health programs.